1995
DOI: 10.1108/07358549510102767
|View full text |Cite
|
Sign up to set email alerts
|

Public attitudes toward the police

Abstract: Surveys attitudes to police (ATP) in Santa Ana, California by asking respondents what they most like or dislike about police. Finds inter alia that the primary indicator of ATP is how people feel about their location. Contrasts sharply with previous research in finding that ethnicity is not a very good predictor of ATP. Points out that unrealistic expectations for law enforcement may be ameliorated by community policing, which involves citizens in decision making and neighborhood improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
142
3
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(154 citation statements)
references
References 10 publications
8
142
3
1
Order By: Relevance
“…Individual attitudinal characteristics also have been shown to influence satisfaction with police. Hindelang [14] found that Republicans held more favorable attitudes towards police than Democrats, a proposition confirmed by Zamble and Annesley and Vaughn [35] . Perhaps these findings reflect poles on an authoritarian/antiauthoritarian continuum.…”
Section: Literature Reviewmentioning
confidence: 86%
“…Individual attitudinal characteristics also have been shown to influence satisfaction with police. Hindelang [14] found that Republicans held more favorable attitudes towards police than Democrats, a proposition confirmed by Zamble and Annesley and Vaughn [35] . Perhaps these findings reflect poles on an authoritarian/antiauthoritarian continuum.…”
Section: Literature Reviewmentioning
confidence: 86%
“…Jesilow, Meyer and Namazzi (1995), for instance, found that ethnicity is not a good predictor of attitudes toward police. Frank and colleagues (1996) actually found that African Americans in Detroit held more favorable views of the police than did White residents.…”
Section: Racementioning
confidence: 99%
“…A growing number of studies, however, question the primacy of race and stress the importance of neighborhood contextual characteristics in shaping citizens' evaluations of police. Some researchers find that the effect of race or ethnicity is not significant when neighborhood contextual variables are simultaneously considered (e.g., Cao et al, 1996;Jesilow, Meyer, & Namazzi, 1995;Sampson & Jeglum-Bartusch, 1998;Schuman & Gruenberg, 1972). Others specifically suggest that neighborhood class status plays an equally important, if not greater, role in determining satisfaction with police (Dunham & Alpert, 1988;Weitzer, 1999Weitzer, , 2000.…”
Section: Introductionmentioning
confidence: 99%
“…If residents' dissatisfaction with the police in disadvantaged communities is in part a function of greater opportunities for and fewer constraints on police misconduct and if these opportunities and constraints are related to the level of crime and disorganization in those communities, then it is reasonable to expect that citizens' opinions of the police will be lower in neighborhoods with high levels of street crime or in places where residents perceive a great deal of crime (Brown and Benedict 2002). Communities whose residents believe that crime is a serious problem in their neighborhoods are more likely than residents of other areas to be critical of the police (Huebner, Schafer, and Bynum 2004;Jesilow, Meyer, and Namazzi 1995;RAND 2005;Weitzer and Tuch 2006), and the same is true for those who report that a violent crime occurred in the neighborhood in the past year (Weitzer and Tuch 2002). The same pattern is evident when the measure is the official crime rate: Areas high in violent crime register lower levels of approval of the police (Murty et al 1990;Reisig and Parks 2000;Sampson and Bartusch 1998;Schafer, Huebner, and Bynum 2003).…”
Section: Neighborhood Crime Disorder and Policingmentioning
confidence: 99%